A Study on The Impact of Welding Parameters on The Tensile Strength of Welded Joints Made of Low Carbon Steel Using Electric Arc Welding - Bakier, Ahmed Faraj; Benisa, Muamar (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
Welding is considered one of the most important industrial processes, so many methods have been developed to obtain a weld joint with good mechanical properties at the lowest cost for different types of metals. The objective of this paper was to study the effect of welding parameters (current, welding wire diameter, and arc Force) on the tensile strength of welded joints of low-carbon steel. The length of the specimen was 200 mm, while the width was 130 mm and the thickness was 6 mm. An arc welding machine (deca E-ARC 860) was used. The experiments were designed based on three levels for each of the currents, the diameter of the welding wire, and the force of the arc. The experiments were carried out by fixing two of the factors changing the third factor, and so on. The test that included the tensile test of the joints was conducted, and compared with a sample of the same non-welding metal. The maximum tensile stress of the welded joint was (203 MPa) with a welding efficiency of (91.44%), and the minimum tensile stress of the welded samples was (138 Mpa) with a welding efficiency of (62.16%).
Keywords: Low carbon steel; Arc welding process; Tensile test